INTERVENSI KELUARGA DALAM PRANATA AGAMA DALAM KONTEKS PERADABAN HINDU - I MADE ARIASA GIRI (Purwadita : Jurnal Agama dan Budaya, 2018)
The family is a place where early citizens are conditioned and prepared for future roles in the adult world. The magnitude of the influence of the role of family and society in education to promote education and civilization, especially if the establishment of good communication between family, school, and community to form students who are well educated from the attitude, behavior, and religion to change the civilization that is more well directed. The support of parents in teaching the ordinances of harmonious relationships in the family, the environment and God through prayer on the application of religious institutions. This has an impact on the formation of a child character who has a strong social perspective principle through the planting of religious content is strong.